Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-01213-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four healthy lifestyle scores for predicting cardiovascular events in a national cohort study

Abstract: The protective effect of different healthy lifestyle scores for the risk of cardiovascular disease (CVD) was reported, although the comparisons of performance were lacking. We compared the performance measures of CVDs from different healthy lifestyle scores among Taiwanese adults. We conducted a nationwide prospective cohort study of 6042 participants (median age 43 years, 50.2% women) in Taiwan’s Hypertensive, Hyperglycemia and Hyperlipidemia Survey, of whom 2002 were free of CVD at baseline. The simple and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 69 publications
0
22
0
2
Order By: Relevance
“…The co-occurrence of smoking, physical inactivity and poor social participation increased cardiometabolic mortality by 3.13 relative to no-risk behaviour 47 . On the contrary, meeting the cardiovascular health metrics and engaging in a healthy lifestyle were associated with lower incidences of CVD, cardiovascular mortality, and all-cause mortality 49 , 50 . Therefore, more emphasis should be placed on interventions targeting multiple lifestyle behaviours.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The co-occurrence of smoking, physical inactivity and poor social participation increased cardiometabolic mortality by 3.13 relative to no-risk behaviour 47 . On the contrary, meeting the cardiovascular health metrics and engaging in a healthy lifestyle were associated with lower incidences of CVD, cardiovascular mortality, and all-cause mortality 49 , 50 . Therefore, more emphasis should be placed on interventions targeting multiple lifestyle behaviours.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the effect of age, a meta-analysis reported that the hazard ratio of CVD increased with increasing age of adults 44 . Younger adults have more cardiovascular benefits from the combined effects of a healthy lifestyle 44 , 50 . Therefore, lifestyle interventions targeted towards younger people are needed to prevent CVD.…”
Section: Discussionmentioning
confidence: 99%
“…In the selected studies on TL, PA was the most studied lifestyle factor, followed by smoking and sleep. In general, being physical active, not smoking and having good sleep quality are associated with a reduced risk of morbimortality for the main chronic diseases [ 8 , 9 , 10 , 11 , 144 , 145 , 146 , 147 ]. There is a challenge in searching for the best biomarker of aging and despite these limitations and the advantage of measuring a combination of biomarkers instead of only one [ 148 , 149 ], TL is the most extensively studied biomarker of age-related diseases [ 7 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The co-occurrence of smoking, physical inactivity and poor social participation increased cardiometabolic mortality by 3.13 relative to no-risk behaviour [46]. On the contrary, meeting the cardiovascular health metrics and engaging in a healthy lifestyle were associated with lower incidences of CVD, cardiovascular mortality, and all-cause mortality [48,49]. Therefore, more emphasis should be placed on interventions targeting multiple lifestyle behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of age, a meta-analysis reported that the hazard ratio of CVD increased with increasing age of adults [43]. Younger adults have more cardiovascular benefits from the combined effects of a healthy lifestyle [43,49]. Therefore, lifestyle interventions targeted towards younger people are needed to prevent CVD.…”
Section: Discussionmentioning
confidence: 99%